Unity of sociological science and practice: lessons from the university lecturer - Хижняк, О. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
To the memory Andryshchenko. A.I.